SYTEMATIC LITERATURE REVIEW : DETERMINAN PENGUNGKAPAN (CSR) PADA PERUSAHAAN PERTAMBANGAN DI INDONESIA - Heni Dwi Susanti; Dwi Cahyono; Astrid Maharani (Bajang Institute, 2021)
This study aims to fill the research gap, knowing, and analyze by providing a systematic literature review of the determinan corporate social responsibility (CSR) disclousure of mining company in Indonesia. This research method uses a systematic literature review process consisting of three stages, namely, planning, implementation and reporting. In the initial search string 916 journal papers were found and 12 journal papers were selected for further research. The results of a systematic literature review of all research contained in journals published from 2016 to 2020 stated that the factors that influence the disclosure of corporate social responsibility in mining companies in Indonesia are very diverse, namely profitability, leverage, liquidity, company size, company growth, ownership. shares, independent commissioners, audit committee, media exposure, foreign ownership, risk minimization, age of publicly owned companies. The most widely used factor in this research is profitability, followed by leverage, where profitability here is an analysis of financial ratios that measures the ability of a company to earn a profit. While leverage is the ability of a management in managing the source of funds, either the wealth of a company or debt.